Сontradiction to public order as a basis for annulment of arbitral award - Akimbekova, S.A.; Moroz, S.P.; Nurtaeva, G.L. (Bulletin of the Karaganda University “Law Series”, 2018)
Arbitration is an alternative way to resolve a dispute. In this article the relationship between the competent court and arbitration shall be articulated, which relationship should be built on the principle of coordination, but not subordination. Moreover, it should be noted that the arbitral awards are final and without appeal. Hence, it follows that the competent court is not a higher authority for arbitration courts, and it shall not be entitled to retry the case on its merits or verify the arbitration award from the point of view of legality and validity. Naturally, in implementing its function of a state to maintain and protect the public order, the public court is still vested with supervisory powers with respect to arbitration court, that being said the competent court can exercise the state control only to the extent and within the framework defined by law. Unfortunately, today in Kazakhstan there are cases when the competent courts complicate the procedure of enforcement by reviewing decisions on the merits, request additional documents that are not prescribed in the statutorily established list of necessary documents. At the same time, the arbitral awards enforcement practice is fairly simple and in reality the decisions of international arbitration courts should be enforced promptly, subject to provision of the full package of necessary documents. In this regard, there is a need to study the «public order» concept. After all, if the courts annul arbitral awards referring to violations of public order without proper justification and without taking international theory and practice into account, this will cause serious harm to the development of arbitration in Kazakhstan. It should be kept in mind that the efficient investment activities require adequate development of arbitration.